Unidades de Conservação de Santa Catarina - Vitali, Mariana; Uhlig, Vivian Mara (Sustainability in Debate, 2010)
This study focuses on the conservation areas of Santa Catarina’s State. The goals are to understand the importance and motivation for the creation of the protected areas, analyze their implementation processes, and their contribution to the conservation scenario for the maintenance of ecological functions and conservation of the State’s natural resources. The methodology used for data collection was based on literature review of secondary’s references sources, interviews with the Environmental Foundation (FATMA) and query the database from the Chico Mendes Institute for Biodiversity Conservation (ICMBio). The results reveal the existence of a minimum legal framework for strengthening the protected areas system studied. However, it shows that not all conservation areas have created the appropriate conditions and support to meet the objectives that justified its creation, pointing out weaknesses that require review and incorporation of actions to become public policies of protected areas more effective.